Discovery of a potent olaparib–chlorambucil hybrid inhibitor of PARP1 for the treatment of cancer - Qin, Hongyu; Zhang, Jian; Zhao, Yilu; Zhang, Lihui; Feng, Jinhong; Zhang, Lei (Frontiers in Pharmacology, 2023)
Development of Poly (ADP-ribose) polymerase (PARP) inhibitors has been extensively studied in cancer treatment. Olaparib, the first approved PARP inhibitor, showed potency in the inhibition of both BRCA (breast cancer associated)-mutated and BRCA-unmutated cancers. Aiming to the discovery of olaparib analogs for the treatment of cancer, structural modifications were performed based on the scaffold of olaparib. In the first series, reduction of carbonyl group to CH2 led to decrease of PARP1 inhibitory activity. Preserving the original carbonyl group, molecules with potent PARP1 inhibitory activities were derived by introduction of hydrazide and aromatic nitrogen mustard groups. It is remarkable that, molecule C2 with chlorambucil substitution, exhibited broad-spectrum anticancer activities in the in vitro antiproliferative assay. Compared with olaparib and chlorambucil, molecule C2 also showed significant potency in inhibition of a variety of BRCA-unmutated cell lines. Further analysis revealed the effects of C2 in induction of G2/M phase cell cycle arrest and promotion of apoptosis. Collectively, the olaparib-chlorambucil hybrid molecule (C2) could be utilized as a lead compound for further drug design.